Evolution of the use of programming languages and digital Tools in Spanish data journalism - Ribera-Carbonell, Enrique; Arias-Robles, Félix (Estudios sobre el Mensaje Periodístico, 2025)
Data journalism is one of the most promising specialties with the greatest potential in the media, but also one of the most technically demanding. Programming languages and digital tools acquire a special role here and require greater efforts in training journalists. To analyze the evolution of the use of programming and digital tools in Spain, a longitudinal field study was carried out in two stages. First, a professional from each media outlet with a well-established data journalism team was interviewed, resulting in a total of 10 interviews in 2021. This process was repeated in 2024 with a total of 8 professionals from 8 media outlets to observe their evolution over those three years. The results of this research show that R, Python and JavaScript are the most used languages in Spanish newsrooms for producing data-based journalistic pieces, while Excel, Google SpreadSheets, Datawrapper and Flourish are the tools most valued by journalists for data acquisition, cleaning, analysis, and visualization. Additionally, it was observed that AI is an emerging technology that, although used cautiously by journalists, is mainly used in code creation and curation, as it has not yet produced fully reliable results in the data analysis test they have conducted.